Evolutionary model and risk analysis of environmental geological disaster chain in open-pit mine under complex network - Feng, Dongmei; Zhang, Jing; Wang, Jing (Frontiers in Earth Science, 2025)
The environmental geological disaster of open-pit mine poses a great threat to the safety of surrounding residents, the stability of urban social economy and the sustainable development of ecological environment. By combining disaster system theory with complex network theory, this study built a network evolution model including 45 distinct disaster nodes and 71 connecting edges through the analysis of disaster-pregnant environment, disaster-causing factors and disaster-bearing body of open-pit mine environmental geological and identified key nodes and connecting edges in the network according to the structural characteristics of the complex network. The results indicate that the environmental geological disasters of open-pit mine are composed of source disaster events, chain-generated disaster events, and final disaster events. By controlling the key nodes of chain disasters such as road disruption, inconvenient living conditions and water pollution, or by cutting off road disruption → traffic obstruction, inconvenient living conditions → disturb social stability, vegetation destruction → soil erosion, soil erosion → degradation of soil function, drainage pipe rupture → poor drainage and other key links of the chain-generated, can effectively control or cut off the network transmission path of the environmental geological disaster chain of open-pit mine. The research results can provide scientific basis for environmental geological disaster control and chain-breaking in open-pit mine, and help to ensure the safety of open-pit mining areas and promote the sustainable development of mining cities.